Landscape-ecological zoning landscapes of medium-high mountains of the Southern Ural - Psyanchin A.V. (Naučno-Tehničeskij Vestnik Brânskogo Gosudarstvennogo Universiteta, 2018)
The problems of landscape-ecological zoning landscapes of medium-high mountains of the Southern Urals, the analysis of the work of researchers in physical-geographical zoning and applied, developed and supplemented by methods of landscape-ecological zoning, the scheme of the landscape-ecological zoning landscapes of medium-high mountains of the Southern Urals.